Percy Jackson's Greek heroes - Riordan, Rick (Disney-Hyperion, 2017)
Percy Jackson, son of Poseidon and modern-day demi-god, offers his unique viewpoint and retelling of a range of ancient Greek myths, including the stories of heroes like Jason and Theseus, as well as Perseus, Atalanta, and Bellerophon. Presents companion material to the "Percy Jackson" series of books.